Current Treatment Patterns and the Role of Upfront Autologous Stem Cell Transplantation in Patients with Peripheral T-Cell Lymphoma: A Korean Nationwide, Multicenter Prospective Registry Study (CISL 1404) - Cho, Hyungwoo; Yoon, Dok Hyun; Shin, Dong-Yeop; Koh, Youngil; Yoon, Sung-Soo; Kim, Seok Jin; Do, Young Rok; Lee, Gyeong-Won; Kwak, Jae-Yong; Park, Yong; Kim, Min Kyoung; Kang, Hye Jin; et al. (Cancer research and treatment, 2023)
Purpose We conducted a nationwide, multicenter, prospective registry study for newly diagnosed patients with peripheral T-cell lymphoma (PTCL) to better define the clinical characteristics, treatment patterns, survival outcomes, and the role of upfront autologous stem cell transplantation (ASCT) in these patients.Materials and Methods Patients with PTCL receiving chemotherapy with curative intent were registered and prospectively monitored. All patients were pathologically diagnosed with PTCL.Results A total of 191 patients with PTCL were enrolled in this prospective registry study. PTCL, not otherwise specified (PTCL-NOS) was the most common pathologic subtype (n=80, 41.9%), followed by angioimmunoblastic T-cell lymphoma (AITL) (n=60, 31.4%). With a median follow-up duration of 3.9 years, the 3-year progression-free survival (PFS) and overall survival (OS) rates were 39.5% and 60.4%, respectively. The role of upfront ASCT was evaluated in patients who were considered transplant-eligible (n=59). ASCT was performed as an upfront consolidative treatment in 32 (54.2%) of these patients. There were no significant differences in PFS and OS between the ASCT and non-ASCT groups for all patients (n=59) and for patients with PTCL-NOS (n=26). However, in patients with AITL, the ASCT group was associated with significantly better PFS than the non-ASCT group, although there was no significant difference in OS.Conclusion The current study demonstrated that the survival outcomes with the current treatment options remain poor for patients with PTCL-NOS. Upfront ASCT may provide a survival benefit for patients with AITL, but not PTCL-NOS.